Haploinsufficiency of COQ4 causes coenzyme Q10 deficiency. Issue 3 (24th February 2012) - Salviati, Leonardo; Trevisson, Eva; Rodriguez Hernandez, Maria Angeles; Casarin, Alberto; Pertegato, Vanessa; Doimo, Mara; Cassina, Matteo; Agosto, Caterina; Desbats, Maria Andrea; Sartori, Geppo; Sacconi, Sabrina; Memo, Luigi; et al.
Abstract : Background: COQ4 encodes a protein that organises the multienzyme complex for the synthesis of coenzyme Q10 (CoQ10 ). A 3.9 Mb deletion of chromosome 9q34.13 was identified in a 3-year-old boy with mental retardation, encephalomyopathy and dysmorphic features. Because the deletion encompassed COQ4, the patient was screened for CoQ10 deficiency. Methods: A complete molecular and biochemical characterisation of the patient's fibroblasts and of a yeast model were performed. Results: The study found reduced COQ4 expression (48% of controls), CoQ10 content and biosynthetic rate (44% and 43% of controls), and activities of respiratory chain complex II+III. Cells displayed a growth defect that was corrected by the addition of CoQ10 to the culture medium. Knockdown of COQ4 in HeLa cells also resulted in a reduction of CoQ10. Diploid yeast haploinsufficient for COQ4 displayed similar CoQ deficiency. Haploinsufficency of other genes involved in CoQ10 biosynthesis does not cause CoQ deficiency, underscoring the critical role of COQ4 . Oral CoQ10 supplementation resulted in a significant improvement of neuromuscular symptoms, which reappeared after supplementation was temporarily discontinued. Conclusion: Mutations of COQ4 should be searched for in patients with CoQ10 deficiency and encephalomyopathy; patients with genomic rearrangements involving COQ4 should be screened for CoQ10 deficiency, as they could benefit from supplementation.